COCTAILL - Elena Volodina; Ildikó Pilán (University of Gothenburg, 2025)
Corpus of coursebooks used for teaching L2 Swedish. Annotated manually for text structure and pedagogical/didactical categories; automatically linguistically annotated. See more here https://spraakbanken.gu.se/forskning/teman/icall/icall-l2-projects/l2-data

Korpus av kursböcker för undervisning av L2-svenska. Annoterade manuellt för textstruktur och pedagogiska/didaktiska kategorier; automatiskt uppmärkt med språkvetenskapliga annoteringar. Se mer här https://spraakbanken.gu.se/forskning/teman/icall/icall-l2-projects/l2-data
COCTAILL
Keywords: Language Technology (Computational Linguistics); course books; language learning; Swedish learner language; corpus; Languages and Literature; Språk och litteratur; Natural Language Processing; Språkbehandling och datorlingvistik